Anti-vascular endothelial growth factor treatment in diabetic macular edema - Kim M (Dove Medical Press, 2016)
Moosang KimDepartment of Ophthalmology, School of Medicine, Kangwon National University, Chuncheon, KoreaWe read with great interest the article titled “Clinical effects and safety of treating diabetic macular edema with intravitreal injection of ranibizumab combined with retinal photocoagulation” by Yan et al.1 We congratulate the authors for this well-organized study and would like to contribute to their findings.   The Early Treatment Diabetic Retinopathy Study demonstrated that focal laser for diabetic macular edema (DME) effectively halved the percentage of eyes that experienced vision loss and doubled the percentage of eyes that achieved visual gain.2 Until the past decade, focal laser photocoagulation was the standard of care for treating DME.